The difficulties of implementing palliative care - Mariângela Ferraz Rodrigues Araújo (2022)
Palliative Joint Care (PC) is a set of palpable care practices that aim to prevent patients from increasing patients with diseases or a more advanced stage according to their disease. Care is provided by a multidisciplinary team, composed of nurses, nutritionists, nutritionists, doctors, whose purpose is to relieve autonomy, making what has one and the patient possible to prepare the death in their own way. The study aims to analyze the importance through qualitative data and what are the difficulties for the implementation of palliative care in the Adult Intensive Care Unit (ICU). It consists of a literature review, through a bibliographic survey, with an exploratory and relative approach, not on the physiotherapeutic performance in palliative care within the same Intensive Care (ICU) system, and how the environment among professionals is seen and graphic care multidisciplinary teams within hospitals. Realizing the importance of palliative care for critically ill patients, endorsing the phases of the patient's importance, was possible, in addition to the importance in this process. The prioritization of the patient's well-being in an intensive environment is always the focus of the treatment from the initial point, until its delivery, always maximizing its intention, psychological and physical health in a global way, where all the professionals involved are of paramount importance. with responsibility.